1997
DOI: 10.1021/jp9628951
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystal Structures, Molecular Mechanics Calculations, and Calculations of the Nonlinear Polarizabilities (β and γ) of Dicyanovinylbenzene and Its Methoxy Derivatives, and Comparison with Experimental Values of β

Abstract: X-ray single-crystal study, molecular mechanics calculations, and calculations of the static nonlinear polarizabilities (β and γ) were performed for dicyanovinylbenzene and series of its mono- and dimethoxy-substituted derivatives. X-ray analysis has been done for dicyanovinylbenzene, its o- and p-methoxy- and 2,4-dimethoxy-substituted derivatives together with corresponding EFISH measurements of the β values for these compounds. Nonlinear polarizabilities were calculated for all series of the mono- and disubs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 54 publications
8
29
0
Order By: Relevance
“…To calculate important NLO molecular electronic characteristics (dipole moments and second-order polarizabilities β) we have used the technique described in detail in our previous paper. 17 It was shown that the values of β calculated with the experimental X-ray geometries, as well as obtained using quantum-chemical or molecular mechanics optimized geometry parameters, are very close in most cases. So, the easiest way to estimate a priori some molecular electronic properties for a large series of compounds is the molecular mechanics calculation of the optimal molecular geometry and semiempirical quantum-chemical calculation of their electronic properties.…”
Section: Calculation Of the Static Polarizabilities (β)mentioning
confidence: 85%
See 3 more Smart Citations
“…To calculate important NLO molecular electronic characteristics (dipole moments and second-order polarizabilities β) we have used the technique described in detail in our previous paper. 17 It was shown that the values of β calculated with the experimental X-ray geometries, as well as obtained using quantum-chemical or molecular mechanics optimized geometry parameters, are very close in most cases. So, the easiest way to estimate a priori some molecular electronic properties for a large series of compounds is the molecular mechanics calculation of the optimal molecular geometry and semiempirical quantum-chemical calculation of their electronic properties.…”
Section: Calculation Of the Static Polarizabilities (β)mentioning
confidence: 85%
“…In our previous paper 17 we reported X-ray crystal structures, molecular mechanics calculations, and calculations of the nonlinear polarizabilities (β and γ) for dicyanovinylbenzene and a series of some of its methoxy-substituted derivatives (with o-methoxy, p-methoxy, and 2,4-dimethoxy substituents). This class of organic chromophores represents an interest in NLO material studies because of the well-known efficiency of the -CHdC(CN) 2 group as an electron acceptor with an extended conjugation chain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One such compound is the donor±acceptor substituted benzene derivative N-[2-(dimethylamino)-5-nitrophenyl]acetamide, (III), which crystallizes in a non-centrosymmetric space group and which therefore allows second-harmonic generation (Baumert et al, 1987;Norman et al, 1987). As a part of a search for new NLO materials (Antipin et al, 1997(Antipin et al, , 1998, we synthesized two new compounds, N-[2-(isopropylamino)-5-nitrophenyl]acetamide, (I), and N-[2-(butylamino)-5-nitrophenyl]acetamide, (II), which are analogous to (III). In this work we present the results of structural investigations of the compounds (I), (II) and (III).…”
Section: Commentmentioning
confidence: 99%